INFLUENCE OF BENZYL AMINO PURINE ON SHOOT PRODUCTION THROUGH IN VITRO SHOOT TIP CULTURE OF CUCUMBER - Faisal, S.M.; Haque, Md. Shahidul; Nasiruddin, K. M. (Malaysian Journal of Science, 2011)
Multiple shoot production ability of some commercial cucumber varieties were assessed. Four varieties of cucumber such as Shila, Green Field, Shital and shahi-50 and four BAP concentrations such as 0.0, 1.0, 3.0 and 5.0 mg/l were tested against this investigation. Different cucumber varieties and BAP concentrations showed significant effects in all the parameters studied. All the varieties regenerated maximum number of explants when they were cultured on Murashige and Skoog media supplemented with BAP @ 3.00 mg/l which was followed by the BAP @ 5.00 mg/l. Variety Green Field took the shortest time (6.11 days) for shoot initiation when it was cultured on BAP @ 3.00 mg/l enriched Murashige and Skoog media. Variety Green Field produced the highest number of multiple shoots regardless of BAP concentrations except control at second subculture but at third subculture all the varieties produced more than double number of multiple shoots regardless of BAP concentrations except BAP free media. (Keywords : Multiple shoot, in vitro, shoot tip and subculture.)